Medical improvisation training to enhance the antenatal counseling skills of neonatologists and neonatal fellows: a pilot study - Sawyer, Taylor; Fu, Belinda; Gray, Megan; Umoren, Rachel (The journal of maternal-fetal & neonatal medicine, 2017)
Neonatologists must be skilled at providing antenatal counseling to expectant parents of premature infants at the limits of viability. We conducted a medical improvisation workshop with the objective of enhancing antenatal counseling skills. Pre- and postworkshop questionnaires were collected to examine the impact of the training. A follow-up survey was distributed 3 months after the workshop to examine the impact of the training on antenatal counseling skills. Nine neonatologists and three neonatal fellows participated in the workshop. Participants reported the skills learned in the workshop could enhance the quality of antenatal counseling. On follow-up survey, 90% of subjects reported improvements in the quality of their antenatal counseling. Participation in a medical improvisation workshop resulted in enhancements of self-perceived antenatal counseling skills. Medical improvisation training may provide a feasible and effective method of communication training for neonatologists. Further research into this innovative method are needed.